Relações entre população folicular antral, hormônio anti-Mülleriano, mastite e fertilidade em bovinos - Pinto, Tássia Louregiani Carvalho (2018)
In the selection of dairy cows, fertility is one of the most relevant aspects. Resistance to infections and milk quality must be included with fertility in selection programs. The objective was to evaluate the relations among antral follicle count (AFC), anti-Müllerian hormone (AMH), mastitis and fertility in taurine and zebu cows. In trial 1, carried out in Raleigh, NC-EUA, Jersey (n = 22) and Holstein (n = 57) lactating cows were used. In experiments 2 and 3, 80 Girolando, and 39 Gir cows from EPAMIG were used. All cows, with at least 20 days post-partum and a maximum of 28 days into gestation, were ultrasounded to assess AFC, measured for vulvar width and blood sampled for AMH. Reproductive and somatic cell count (SCC) were obtained from DHIA and EPAMIG. Data were analyzed using SAS® (Cary, NC- EUA) which were normalized when necessary. The effects of vulvar width, AFC and AMH classes on fertility and mastitis-related (SCC) data were evaluated through the GLIMMIX procedure with the proper predefined distributions and transformations required. Simple (PROCREG) and multivariate (JMP-SAS®, Cary, NC-EUA) procedures were used to investigate relations among the variables. A generalized regression model (JMP-SAS®, Cary, NC-EUA) was used to test the effects of AMH, AFC, parity and age classes on reproductive and mastitis-related variables. In experiment 1, AMH concentrations and AFC were positively correlated in the Holstein (r = 0.66; P < 0.0001) and Jersey (r = 0.68; P = 0.0005) breeds, respectively. Considering both breeds (n = 79) there were positive correlations between AFC and vulvar width (r = 0.26; P = 0.02) and between AFC and AMH (r = 0.62; P < 0.0001). Post-partum interval (PPI) was shorter (P < 0.0001) in the high AMH class (352.68 ± 4.13 days) compared to the low AMH class (379.69 ± 5.38 days), and it was also longer (P < 0.05) in the large (372.47 ± 4.85 days) compared to the small (359.52 ± 4.57 days) vulvar width class. The classes studied in experiment 1 did not influence SCC and the number of services per conception. In experiment 2, the calving interval was not influenced by AMH class, but was shorter (P < 0.05) in the small (418.96 ± 3.17 days) compared to the large (444.10 ± 4.58 days) vulva class. Milk somatic cell count (cells/mL) was higher (P < 0.05) in the low AMH class (187,813.00 ± 94.16 vs 409,951.00 ± 117.57) and in the small vulva class (352,726.00 ± 111.05 vs 218,284.00 ± 98.59). There was a positive correlation (r = 0.53; P < 0.0001) between CFA and vulva width. In experiment 3 AMH and CFA were positively correlated (r = 0.51; P < 0.04). In conclusion, some relationships among AMH, AFC and vulva width were indicative of fertility and udder health, which sets grounds for possible consideration in selection for dairy cows fertility, as long as, studies with larger numbers of cows are done.